Socio-economic analysis of agroforestry systems in semi-arid tropics - Doddabasawa, .; Chittapur, B.M.; Kammar, Shivanand K. (Indian Journal of Agroforestry, 2020)
Agroforestry is a dynamic, ecological based natural resource management system that diversifies economical and ecological benefits. However, resource preferences in the agroforestry are influenced by the needs of household livelihood dependency and socio-economic status of farmers. The present study revealed that majority of farmers practiced bund (50%), followed by boundary planting (22.2%) and silvi-horti system (20.8%), and density of trees (ha-1) varied from 80 to 150 ha-1. Chi-square test found significant association between tree density and farmers preference of growing trees to size of land holding, net income, energy source and livestock population. Further, farmers preferred trees for productive value such as timber, fuel wood, fruit and fodder over protective values. The majority of the respondent expressed competition with crop, followed by small land holding size and lack of marketing facility as major constraints for growing trees on the farm-land.